(untitled) (Journal of the College of Education for Women, 2019)
The research(the internal and external factors affecting the political system inPAKISTAN) involves a series of effects interact both internally and external to affect thestsbility of the political system.Intrernally there are a lot of powers affecting the political map of PAKISTAN such asmilitary institution, political parties, judgement, religious schools……etc.of internalfactors, which represent one of the most important pressure points on the system.Externally one of the most important external factors which affect internal stability isPakistani allision to USA in antiterrorism war. The Pakistani military institution wasinvolved in the war against Pakistani tribes leading to unstable security in Pakistan,leading to lessen the popularity of Gen.MUSHARAF who ruled Pakistan 1999-2008.Gen.MUSHARAF took the responsibility of fighting terrorism in cooperation withUSA, this was on of his mistakes during ruling Pakistan which made the Pakistani peopleto condemn and was a failure in Pakistani policy .Its the same problems of the politicalsystem during the erra of the president (ASSF ZRDARI). This research is involved withthe major problems of the system in parallel with the continuous war againstAFGHANSTAN which has geographical, racial and religious links with Pakistan. Theseproblems are putting shadows on the Pakistani society which supports Afghani Talibanthrough Pakistani Taliban. They have the same strategic goal to push the Americans out ofthe area.